A gene expression-based comparison of cell adhesion to extracellular matrix and RGD-terminated monolayers. (June 2015) - Sobers, Courtney J.; Wood, Sarah E.; Mrksich, Milan
Abstract: This work uses global gene expression analysis to compare the extent to which model substrates presenting peptide adhesion motifs mimic the use of conventional extracellular matrix protein coated substrates for cell culture. We compared the transcriptional activities of genes in cells that were cultured on matrix-coated substrates with those cultured on self-assembled monolayers presenting either a linear or cyclic RGD peptide. Cells adherent to cyclic RGD were most similar to those cultured on native ECM, while cells cultured on monolayers presenting the linear RGD peptide had transcriptional activities that were more similar to cells cultured on the uncoated substrates. This study suggests that biomaterials presenting the cyclic RGD peptide are substantially better mimics of extracellular matrix than are uncoated materials or materials presenting the common linear RGD peptide.